If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x-1/2(2x-4)=2(-2x+5)-8
We move all terms to the left:
-3x-1/2(2x-4)-(2(-2x+5)-8)=0
Domain of the equation: 2(2x-4)!=0We multiply all the terms by the denominator
x∈R
-3x*2(2x-4)-((2(-2x+5)-8))*2(2x-4)-1=0
We calculate terms in parentheses: -((2(-2x+5)-8))*2(2x-4), so:Wy multiply elements
(2(-2x+5)-8))*2(2x-4
-6x^2(2-((2(-2x+5)-8))*2(2x-4)-1=0
| -8(x+4)-7=-3(x-4) | | 41=-7-6n | | 8-7w=3w+9* | | 7=(–1+2x) | | 16m+5+2m=5(2-m)+15 | | 6w+7=12 | | 3n+22=5n+14 | | 5x-3+6x=-80 | | -24-12.3x=13.5-3.6x | | p=17.95+71.80 | | 100=5x+4(x-2) | | 6x+18=3x-1 | | -2x-5=-71 | | -24+3b=3(b-8) | | k+(-5)=-14 | | 18=-3x-(-3x+10) | | 4.9x=24.5 | | 2x^-14x+24=0 | | 63=9r | | 2(x-1)-8=7(x-7) | | 3.95+3+8.95b=47.65 | | -7x-7(3x-6)=10+4(-7x+8) | | (-6x+46)+(-9x+29)=180 | | 495=165+55m | | -8x+8=−8x+8 | | 20+(4x-6=6x | | 0=4+w/5 | | 5x+10=3x+2x-8 | | 5z=-8+6z | | x+5=(x–2)–(2x–7 | | -3(x+5+3x)-5(x+5+3x)=24 | | w-2=6.5 |